2019
DOI: 10.1111/ene.13984
|View full text |Cite
|
Sign up to set email alerts
|

Plasma C‐type lectin‐like receptor 2 as a predictor of death and vascular events in patients with acute ischemic stroke

Abstract: Background and purpose C‐type lectin‐like receptor 2 (CLEC‐2) has prominent involvement in platelet activation, which is increased in coronary heart disease and acute ischaemic stroke (AIS) and is associated with stroke progression and stroke prognosis. Here, the aim was to examine the prognostic value of CLEC‐2 in death and vascular event recurrence in AIS patients. Methods In all, 352 patients with AIS were studied prospectively. All patients were followed up for 1 year. Death for all vascular events and a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Two articles originating from the same cohort of AIS patients consisting of 323 individuals with a follow-up of 1 year showed that sCLEC-2 might be used as a predictor for AIS; the elevated level of the biomarker was significantly correlated with stroke progression and death. Patients with the highest sCLEC-2 level had an 8-fold higher risk of progressive stroke or death compared to the patients in the lowest quartile (140,141).…”
Section: Acute Ischemic Strokementioning
confidence: 89%
See 1 more Smart Citation
“…Two articles originating from the same cohort of AIS patients consisting of 323 individuals with a follow-up of 1 year showed that sCLEC-2 might be used as a predictor for AIS; the elevated level of the biomarker was significantly correlated with stroke progression and death. Patients with the highest sCLEC-2 level had an 8-fold higher risk of progressive stroke or death compared to the patients in the lowest quartile (140,141).…”
Section: Acute Ischemic Strokementioning
confidence: 89%
“…Ischemic stroke, not based on cardiac embolism, is predominantly a consequence of atherothrombosis in the carotid and other cranial arteries (130). Platelet activation as measured by release markers during an acute ischemic stroke (AIS) has been demonstrated in many studies, showing elevated plasma levels of sP-selectin (131)(132)(133)(134)(135)(136)(137)(138), sCD40L (134), sGPVI (139), and sCLEC2 (140,141) in comparison to healthy volunteers (Table 4, Supplementary Table 1).…”
Section: Acute Ischemic Strokementioning
confidence: 99%
“…A study conducted on Chinese patients with acute ischemic stroke reported high levels of plasma CLEC-2, which was associated with poor prognosis and significantly increased risk of death (45). Other studies have also shown that plasma CLEC-2 is a predictor of cerebrovascular disease recurrence in patients with acute ischemic stroke (46). Podoplanin inhibitors mitigated the pathological changes after cerebral ischemiareperfusion in a mouse model of middle cerebral artery occlusion-induced stroke, which indicates a potential role of the CLEC-2/podoplanin axis in thromboinflammation (47).…”
Section: Clec-2 In Neurological Diseasesmentioning
confidence: 99%
“…Nonetheless, plasma levels of soluble CLEC-2 (sCLEC-2) could recently be positively correlated with stroke progression, recurrence of vascular events, and risk of death in patients with AIS, making sCLEC-2 a promising prognostic marker for AIS (►Table 1). 102,103…”
Section: Targeting Clec-2 In Ischemic Strokementioning
confidence: 99%